2020
DOI: 10.1159/000505534
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Approach to Evaluate for Cardiac Metastasis in a Case of Non-Small Cell Lung Cancer

Abstract: Malignancies have demonstrated the ability to metastasize to cardiac tissue. However, an optimal diagnostic algorithm for cardiac tumors has not yet been established, due at least in part to the scarcity of symptomatic cases. Several case reports describe how the usage of 18 F-labeled fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) incidentally revealed cardiac neoplasia. This modality, which indicates uptake sites of the radioisotope 18 F-FDG, allows for whole-body imaging and is often used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…They can reduce the specificity, making it crucial to consider the clinical context. Bilani et al [11] reported a case of a false positive cardiac uptake, later confirmed by CMR. They also highlighted the challenge of pseudoprogression under immunotherapy, which can often manifest in the early months of treatment and, in some cases, even later.…”
Section: Discussionmentioning
confidence: 99%
“…They can reduce the specificity, making it crucial to consider the clinical context. Bilani et al [11] reported a case of a false positive cardiac uptake, later confirmed by CMR. They also highlighted the challenge of pseudoprogression under immunotherapy, which can often manifest in the early months of treatment and, in some cases, even later.…”
Section: Discussionmentioning
confidence: 99%
“…The more experienced the person performing the echocardiographic studies, the higher the likelihood of picking up even smaller abnormalities. It is also important to note that often the test is being done for other reasons but incidentally picks up the suspected cardiac metastases [19,[20][21][22]. Other investigations such as Cardiac Ultrasound (CUS), CT Scan and magnetic resonance imaging (MRI) are also useful for further definition and confirmation.…”
Section: Investigations and Managementmentioning
confidence: 99%
“…MRI also gives better definition of the surrounding structures, which is crucial in the assessment of spread. PET (Positron emission tomography) scans are at times used because it is part of the armamentarium of tests for working up the primary cancer, such as head and neck cancers [20,21]. Chest Xrays are usually non-specific and may show cardiomegaly and at times, prominence of the azygous vein if pericardial effusion is present.…”
Section: Investigations and Managementmentioning
confidence: 99%